Dizziness from a neurological Point of View - Erbguth, Frank Joachim (Deutsche Medizinische Wochenschrift, 2023)
Vertigo has many different causal disorders, ranging from general dizziness and orthostatic regulation disorders to attacks of rotary vertigo. A targeted anamnesis and clinical examination can be used to narrow down the differential diagnosis. Questions about the type of dizziness, the duration and accompanying symptoms must be clarified. Various methods are used for differentiation in clinical examinations: the head impulse test, testing of the vertical divergence of the eyes, positioning maneuvers and the ability to stand and walk. But diagnostic imaging is also important. MRI can be used to confirm or rule out vascular causes (cerebral infarction or minor bleeding) and inflammatory lesions. Because the most serious misdiagnosis of dizziness is overlooking a stroke.
CRIS-Team WoS Importer:2023-03-31